Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/ctr.13885
|View full text |Cite
|
Sign up to set email alerts
|

De novo thrombotic microangiopathy in two kidney transplant recipients from the same deceased donor: A case series

Abstract: Thrombotic microangiopathy (TMA) is a recognized and serious complication of renal transplantation. Atypical hemolytic uremic syndrome (aHUS), a subset of TMA, occurs in the setting of dysregulation of the alternative complement pathway and can cause disease in native kidneys as well as recurrence in allografts. De novo TMA represents a classification of TMA post‐transplant in the absence of clinical or histopathological evidence of TMA or aHUS in the native kidney. De novo TMA is a more heterogeneous syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It may also develop later, within a few years of transplantation, and presents more heterogeneous manifestations than aHUS. 22,23 A review of 15 870 kidney transplant recipients in the United States Renal Data System (USRDS) by Reynolds et al 24 revealed that the rates of de novo TMA vary from 1.1% to 14%. Langer et al reported an incidence of 1.5% for de novo TMA, wherein TMA was diagnosed based on the laboratory parameters.…”
Section: Diagnosis Of Tma In Kidney Transplant Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also develop later, within a few years of transplantation, and presents more heterogeneous manifestations than aHUS. 22,23 A review of 15 870 kidney transplant recipients in the United States Renal Data System (USRDS) by Reynolds et al 24 revealed that the rates of de novo TMA vary from 1.1% to 14%. Langer et al reported an incidence of 1.5% for de novo TMA, wherein TMA was diagnosed based on the laboratory parameters.…”
Section: Diagnosis Of Tma In Kidney Transplant Patientsmentioning
confidence: 99%
“…Recently, Roberts et al 22 documented 2 cases of de novo TMA that occurred immediately following a kidney transplantation in patients who received a kidney graft from the same deceased donor. The authors speculated that deceased donor-related factors could be risk factors for the recipients developing de novo TMA.…”
Section: Amr-associated De Novo Tmamentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes range from transient renal dysfunction with mild clinical significance to acute renal failure requiring temporary dialysis therapy, potential allograft loss, and patient mortality. The outcome depends on the histopathological severity of the TMA, the promptness of the diagnosis, and the initiation of treatment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although rare in kidney transplant recipients, with an incidence of 5.6 cases per 1000 renal transplant recipients per year, TMA is a serious complication in these patients. It associates with poor outcomes, both on kidney allograft and patient [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%